THE INFLUENCE OF SERVICE QUALITY AND RELATIONSHIP QUALITY ON PRIORITY CUSTOMER TRUST OF BANK BJB WEST JAVA REGIONAL OFFICE - Mulyana, Agus (Dinasti Publisher, 2022)
The purpose of this research is to know and analyze: (1) Service Quality; (2) Relationship Quality; (3) Customer Trust; and (4) The Effect of Service Quality and Relationship Quality on Customer Trust in Priority Customers of Bank BJB West Java Regional Office, either simultaneously or partially. The research method used in this study was a descriptive survey and an explanatory survey. The unit of analysis in this study was 56 Priority Customers of Bank BJB West Java Regional Office. The type of investigation is causality in this study is Explanatory. Based on the results of the study, it was obtained that the Quality of Service according to Priority Customers of Bank BJB West Java Regional Office, in fact gave good analysis results, Quality of Relationship of Priority Customers with Bank BJB West Java Regional Office in general can be said to be good. Priority Customer Confidence in Bank BJB West Java Regional Office is currently considered good. Quality of Service and Quality of Relation to Customer Trust Priority Bank BJB West Java Regional Office has a significant effect simultaneously or partially. However, partially the dominant relationship quality influences trust rather than service quality Because Relationship Quality is more dominant in influencing Customer Trust, it is the first priority in increasing Priority Customer Trust of Bank BJB West Java Regional Office, it is advisable for Bank BJB West Java Regional Office to remain consistent in maintaining its existing marketing conditions, so that the performance of Bank BJB West Java Regional Office is increasingly getting better